Feminicide. Questioning the Body of Christ (Teología, 2016)
This article considers feminicide as a contemporary crucifixion, in which the broken Body of Christ reveals itself, and requires that we re-imagine the mystical Body of Christ in a way that may offer a credible story of hope. To take up this task, we must first make clear the significance of feminicide and its growth in the different Latin American countries. Though feminicides in Ciudad Juarez have been the most widely studied, this also happens in Guatemala, Honduras, Peru, and Argentina, amongst other countries. These feminicides demand theology’s attention today. Secondly, we shall look through in which way these assassinations are crucifixions and examples of the broken Body of Christ, and what difference the fact of promoting these theological statements represents. The last section of this work considers the significance of re-imagining the mystic body of Christ in a way that makes hope plausible.
Keywords: Feminicide; Crucifixion; Body of Christ; Hope